Pain Research Forum: application of scientific social media frameworks in neuroscience - Das, Sudeshna; Mccaffrey, Patricia G.; Talkington, Megan; Andrews, Neil; Corlosquet, Stephane; Ivinson, Adrian J.; Clark, Tim (Frontiers in Neuroinformatics, 2014)
Background: Social media has the potential to accelerate the pace of biomedical research through online collaboration, discussions and faster sharing of information. Focused web-based scientific social collaboratories such as the Alzheimer Research Forum have been successful in engaging scientists in open discussions of the latest research and identifying gaps in knowledge. However, until recently, tools to rapidly create such communities and provide high-bandwidth information exchange between collaboratories in related fields did not exist. Methods: We have addressed this need by constructing a reusable framework to build online biomedical communities, based on Drupal, an open-source content management system. The framework incorporates elements of Semantic Web technology combined with social media. Here we present, as an exemplar of a web community built on our framework, the Pain Research Forum (PRF). PRF is a community of chronic pain researchers, established with the goal of fostering collaboration and communication among pain researchers. Results: Launched in 2011, PRF has over 1,300 registered members with permission to submit content. It currently hosts over 150 topical news articles on research; more than 30 active or archived forum discussions and journal club features; a webinar series; an editor-curated weekly updated listing of relevant papers; and several other resources for the pain research community. All content is licensed for reuse under a Creative Commons license; the software is freely available. The framework was reused to develop other sites, notably the Multiple Sclerosis Discovery Forum and StemBook. Discussion: Web-based collaboratories are a crucial integrative tool supporting rapid information transmission and translation in several important research areas. In this article, we discuss the success factors, lessons learned and ongoing challenges in using PRF as a driving force to develop tools for online collaboration in neuroscience.